IDENTIFICATION OF SUITABLE BIVOLTINE FOUNDATION CROSS FOR SUSTAINABLE BIVOLTINE SILKWORM SEED CROP IN TROPICS - S. M. MOORTHY; K. MANDAL; N. B. KAR; S. K. DAS (The Bioscan, 2011)
The success of rearing with presently available conventional bivoltine breeds are unpredictable in some of the seed crop seasons in West Bengal and similar regions of India because of prevailing of highly fluctuating adverse climatic conditions. Thus, it is very much essential to have a bivoltine breed, which can give stable cocoon crop under variable environments. As single bivoltine parent shown poor cocoon yield in those seasons, as an alternative, foundation crosses (FC) were tried. Out of nine FCs evaluated, D6 (P) N x SK4C shown higher cocoon yield of 12.8kg/10000 larvae with 91% pupation (average of three seasons) compared to 9.8kg cocoon yield/10000 larvae with 67% pupation in control, NB18 x P5. Thus the identified FC can be utilized as a male parent for preparation of three way cross, multi x bi hybrid for utilization in commercial crop.